DEVELOPMENT OF ANIMATION-BASED VIDEO MEDIA DIGITAL LITERACY STIMULATES THE LANGUAGE ABILITY OF EARLY CHILDREN - Astutik, Kurniah; Fawait, Agus (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to analyze and understand the Development of Digital Literacy-Based Animation Video Media to Stimulate Language Ability in Early Childhood. This study uses the Research and Development development model. Data analysis techniques consist of validation data analysis, practicality data analysis, attractiveness data analysis, and data analysis on the effectiveness of animated video products. The results of the percentage validity of the media, the results of individual trials, the results of small group trials and the results of large group trials were included in the very practical, interesting and effective categories. Based on the results of the validity of material experts, media experts, linguists and instruments that have been filled in to determine the level of practicality, attractiveness and effectiveness, digital literacy-based animated video media is appropriate and appropriate for use in the process of learning activities to stimulate language skills in early childhood.